1998
DOI: 10.1111/j.1751-1097.1998.tb05220.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen‐bonding and Proton Transfer Interactions between Harmane and Trifluoroethanol in the Ground and Excited Singlet States

Abstract: A study of the hydrogen‐bonding and proton transfer reactions of the ground and excited states of harmane (1‐methyl‐9H‐pyrido/3,4‐b/indole) and its N9‐methyl derivative with 2,2,2‐trifluoroethanol in cyclohexane is reported. Spectral measurements (UV–visible, Fourier trans‐form IR, steady‐state and time‐resolved fluorescence) show the formation of fluorescent ground‐state hydrogen‐bonded complexes. The results have been interpreted assuming a tautomeric equilibrium between a 1:1 hydrogen‐bonded complex and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
36
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 30 publications
2
36
0
Order By: Relevance
“…Spectral Features of the ␤-Carbolines-The photophysical and photochemical properties of some ␤-carbolines have been studied in the literature (11)(12)(13). Some of these are phototoxic to bacteria and insects; Larson et al (11) have found the ability to kill test organisms to vary in the order I Ͼ II Ͼ IIa, and IIb to be inactive.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spectral Features of the ␤-Carbolines-The photophysical and photochemical properties of some ␤-carbolines have been studied in the literature (11)(12)(13). Some of these are phototoxic to bacteria and insects; Larson et al (11) have found the ability to kill test organisms to vary in the order I Ͼ II Ͼ IIa, and IIb to be inactive.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the ␤-carbolines have been shown to be phototoxic to bacteria and insects (11), and attempts have been made to correlate their phototoxicity with their ability to produce reactive oxygen species upon irradiation, i.e. photodynamic or sensitizer abilities (11)(12)(13). On the other hand, there have been reports (14 -16) that some of these Maillard products are antioxidative in nature.…”
mentioning
confidence: 99%
“…These second complexes, with a stoichiometry of at least 1:2, are called the proton transfer complexes (PTC), N dþ Á Á ÁHÁ Á ÁO dÀ . The existence of a charge separation in the PTC complex has been confirmed by FTIR studies on the fundamental stretching frequency of the hydroxylic group of the alcohols [52]. Thus, upon the addition of the betacarboline derivative, the OH stretching band of HFIP decreases and a continuum absorption in the middle region of the spectra is observed.…”
mentioning
confidence: 60%
“…Among the great variety of substrates possessing potential hydrogen bond donor/acceptor sites, the betacarboline ring, 9H-pyrido [3,4-b]indole (BC) [20] (Scheme 19.1), has been widely studied [21][22][23][24][25][26][27][28][29][30][31][32][33]. These rings are the structural units of numerous naturally occurring alkaloids that possess a wide range of biological and pharmacological properties [34][35][36][37][38][39][40][41][42][43][44][45].…”
mentioning
confidence: 99%
See 1 more Smart Citation